Methyl jasmonate is transported to distal leaves via vascular process metabolizing itself into JA-Ile and triggering VOCs emission as defensive metabolites - Tamogami, Shigeru (Landes Bioscience, 2012)
Plants have developed multifaceted defensive systems against adverse environmental factors. One such recognized system is the production of metabolites in plants. Jasmonic acid (JA) and its metabolite methyl jasmonate (MeJA) are known to play key roles in metabolites production. The role of MeJA as a mobile signal has been established in Arabidopsis and Solanaceae plants. However, it remains largely unclear how MeJA-based signaling is organized via its elicited metabolites. Here, we investigated the signaling ability of MeJA by means of vascular transport using Achyranthes bidentata as an experimental plant. Results showed that MeJA was transported and essentially metabolized into its active form JA-Ile in the distal undamaged leaves accompanied by emission of volatile organic compounds. Results presented and discussed therein provide convincing evidence that MeJA acts as a transportable inter-cellular mobile compound in plants self-defense scheme.